Leaf removal at veraison stage differentially affects qualitative attributes and bioactive composition of fresh and dehydrated grapes of two indigenous Cypriot cultivars - Constantinou, Savvas; Gómez-Caravaca, Ana Maria; Goulas, Vlasios; Fernandez-Gutierrez, Alberto; Koundouras, Stefanos; Manganaris, George A. (My University, 2019)
BACKGROUND: The effect of leaf removal on postharvest performance of dehydrated grapes has been poorly analyzed. The aim of this study was to evaluate the effect of leaf removal at veraison stage on the metabolites of fresh and dehydrated grapes of two indigenous Cypriot cultivars (‘Mavro’ and ‘Xynisteri’), which are destined for the production of ‘Commandaria’, a protected designation of origin (PDO) premium sweet wine. RESULTS: Leaf removal led to a reduction of soluble solids, titratable acidity, aroma potential and most of the phenolic groups in the musts of both cultivars. Dehydration led to a significant increase in all of these parameters in both cultivars, being more pronounced in cv. ‘Mavro’. Interestingly, leaf removal indicated differential response in the dehydrated product of the cultivars examined; liquid chromatography (LC-DAD-qTOF-MS) data showed a significant decrease in phenolic compounds in ‘Xynisteri’ must (from 66.73 to 44.15 mg L −1 ), while ‘Mavro’ must registered similar values of phenolic compounds (from 94.78 to 96.72 mg L −1 ), but with a different distribution among phenolic groups. Intriguingly, flavonols and flavan-3-ols that present significant health-promoting properties showed higher concentrations in the must from dehydrated ‘Mavro’ grapes that were subjected to preharvest leaf removal. CONCLUSIONS: Leaf removal at veraison stage followed by sun drying differentially affected the chemical composition of the examined cultivars. This preharvest application followed by postharvest dehydration was beneficial for cv. ‘Mavro’, while this was not the case for cv. ‘Xynisteri’. The effects of leaf removal in other developmental stages (i.e. pre/post bloom stage) need to be dissected with the ultimate goal of providing an end product with high bioactive content.
Keywords: Aroma potential; Commandaria; Phenolic compounds; Sun drying; Sun drying; Vitis vinifera